CONTEMPORARY FRAUD RESEARCH: THE DEVELOPMENT OF FRAUD IN INDONESIAN JOURNAL - Nanak Andrean Prayoga; Saring Suhendro; Liza Alvia (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2025)
This study aims to provide an overview of the development of fraud research in Indonesia and identify opportunities for fraud research in the future. This research uses the charting the field method to analyze articles based on the type of fraud, proxy, research methodology, population and theory used. This study analyzed 133 articles published in 25 nationally accredited journals. The results found that most of the published articles still discuss fraud in general, followed by financial statement fraud and corruption. This finding contradicts the results of the ACFE (2024) survey which states that 89% of global fraud cases are cases of asset misuse. The proxy for financial statement fraud is dominated by M Score and F Score, while the majority of corruption uses the corruption perception index proxy. Then, the proxy for asset misuse is only proxied by the procurement of goods. However, based on a survey conducted by ACFE (2024), there are 9 asset misuse schemes identified based on 1709 cases, including noncash, billing, expense reimbursement, check and payment tampering, cash on hand, skimming, cash larceny, payroll, register disbursements. In addition, the dominant research method used is the survey method, followed by the analytical method, so future researchers need to consider other research methods that are still little used to explain fraud, such as experiments and literature reviews. The most frequently studied population is local government. However, this condition is not in accordance with the results of the Indonesian Fraud Survey, which shows that the industries most harmed by fraud are the banking, mining and health industries. The most surprising result is that the fraud triangle is the most widely used theory, even in the last five years.